Impact of Age at First Immunisation on Equine Influenza Short and Mid‐Term Protective Antibody Levels in Thoroughbred Foals. (September 2015) - Fougerolle, S.; Legrand, L.; Foursin, M.; D'Ablon, X.; Bayssat, P.; Pronost, S.; Paillot, R.
Abstract : Reasons for performing study: Every year, several equine influenza (EI) epidemics are reported worldwide. Equine influenza vaccination is the most efficient method of prevention; however, not all horses develop sufficient immunity after EI immunisation, increasing the risk of infection, infectious virus excretion and the spread of the disease. Objectives: This study aimed to better understand poor vaccine response mechanisms during the primary EI vaccination. Study design: Cohort study. Methods: The EI humoral immune response was measured in 118 Thoroughbred foals set in 3 different stud farms (SF#1 to SF#3) after the primary course of EI vaccination. All foals were immunised with a recombinant canarypox‐based EI vaccine, following the vaccine manufacturer's recommendations. The age at first vaccination was 4 to 8 months. Sera were tested by single radial haemolysis (SRH) against the A/equine/Jouars/4/2006 EIV strain (Florida clade 2) at the time of the first vaccination (V1), 2 weeks and 3 months after the second immunisation (V2), 2 days and 3 months after the third immunisation (V3). Results: Short (V2 + 2 weeks) and mid‐term (V3 + 3 months) SRH antibody levels were statistically different between the stud farms (P‐value = 0.0011 and 0.003, respectively), with SF#1<SF#3<SF#2 and SF#1 SRH antibody titres below the protection threshold (i.e. 85 mm 2 ) at all time points studied. SRH antibody levels induced by EI vaccination were related to the age of foals at the first immunisation (SF#1 median age 143 days, SF#2 median age 181 days and SF#3 median age 156 days), but were independent of the presence of maternal derived antibodies (MDA; P‐value 0.41). Given the results in SF#1, a booster immunisation (V4) was brought forward to restore protective levels of antibody. Conclusion: Independently of the presence of MDA, the age of foals at first immunisation plays an important role in the establishment of adequate antibody levels. Ethical animal research:  All animal work received ethical approval, and consent was obtained from the owners.Sources of funding:  This study was supported by the Basse‐Normandie Region council (France) and the European Regional Development Fund.Competing interests:  None declared.